K⁰ₛ K⁰ₛ correlations in pp collisions at √s=7TeV from the LHC ALICE experiment - Abelev, B.; Adam, J.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.; Agócs, A.G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad Masoodi, A.; Ahmad, N.; et al. (Elsevier, 2012)
Identical neutral kaon pair correlations are measured in √s = 7 TeV pp collisions in the ALICE experiment. One-dimensional K⁰ₛ K⁰ₛ correlation functions in terms of the invariant momentum difference of kaon pairs are formed in two multiplicity and two transverse momentum ranges. The femtoscopic parameters for the radius and correlation strength of the kaon source are extracted. The fit includes quantum statistics and final-state interactions of the a₀/f₀ resonance. K⁰ₛ K⁰ₛ correlations show an increase in radius for increasing multiplicity and a slight decrease in radius for increasing transverse mass, mt, as seen in ππ correlations in pp collisions and in heavy-ion collisions. Transverse mass scaling is observed between the K⁰ₛ K⁰ₛ and ππ radii. Also, the first observation is made of the decay of the fʼ₂(1525) meson into the K⁰ₛ K⁰ₛ channel in pp collisions.
Keywords: K0S-K0S correlations; pp collisions; https://purl.org/pe-repo/ocde/ford#1.03.03